FRI0318 Two-Year Retention and Effectiveness of IV Abatacept in Real-Life Setting: Results from the Action Study. (10th June 2014) - Nüβlein, H.; Alten, R.; Galeazzi, M.; Lorenz, H.-M.; Nurmohamed, M.; Bensen, W.; Burmester, G.-R.; Peter, H.-H.; Pavelka, K.; Chartier, M.; Poncet, C.; Rauch, C.; et al.
Abstract : Background: Initial results from the real-world ACTION study suggest that abatacept (ABA) is clinically effective and well tolerated in pts with RA, with good pt retention over 12 mths. 1 Objectives: To assess retention rates and the effectiveness of IV ABA over 24 mths in the ACTION study. Methods: ACTION is a 2-yr, international (Austria, Belgium, Canada, Czech Republic, Denmark, Germany, Greece, Italy, the Netherlands), non-interventional cohort of pts with RA who initiated IV ABA between May 2008 and January 2011. ABA retention (and 95% CI) over 24 mths was estimated by Kaplan–Meier and stratified by previous RA therapy. The proportion of pts achieving a moderate or good EULAR response was assessed in pts on ABA at 24 mths (as observed). Safety is reported for all enrolled pts. Results: 1137 pts were enrolled and 1131 pts were evaluable; 122 (10.8%) patients were biologic-naïve and 1009 (89.2%) had failed ≥1 prior biologic agent (out of which, 487/1009 [48.3%] failed 1 anti-TNF and 504/1009 [50.0%] ≥2 anti-TNFs, while 18/1009 [1.8%] failed non anti-TNFs only). Baseline characteristics were similar, but disease duration was numerically shorter in biologic-naïve pts versus pts failing ≥1 prior biologic agent (7.0 vs 11.8 yrs). The overall retention rate (95% CI) at 24 mths was 54.4% (51.3, 57.4). Retention rates at 24 mths were higher in biologic-naïve pts (63.2% [53.2, 71.6]) and pts who failed 1 prior anti-TNF (60.6% [55.9, 64.9]) versus pts failing ≥2 prior anti-TNFs (46.7% [42.0, 51.2]) (Figure). The retention rate was 49.2% (44.0, 54.1) in pts who had failed 2 previous anti-TNFs (n=410) and 35.5% (25.4, 45.7) in pts who failed 3 previous anti-TNFs (n=94). More pts discontinued in later lines of treatment for inefficacy (23.9% in biologic-naïve pts and 35.7% in pts failing ≥1 prior biologic agent) than intolerance/safety (7.0% and 10.6%, respectively). A good or moderate EULAR response was achieved in 95.0% of biologic-naïve pts (n=20) and in 80.2% of pts failing ≥1 prior biologic agent (n=283). There were 111 serious adverse events in 63/1137 (5.5%) pts (28 discontinuations) and 12 deaths, including 4 due to serious infections (sepsis [4 mths after last ABA infusion; pt was receiving tocilizumab]; Pneumocystis jiroveci [4 mths after last ABA infusion, pt had deep vein thrombosis]; pneumonia and urosepsis unrelated to ABA). Serious infections occurred in 26 pts and there were 12 malignancies, 5 serious cardiac disorders and 1 serious hypersensitivity reaction. No TB occurred and 2 opportunistic infections were reported ( Cytomegalovirus and P. jiroveci ). Conclusions: In this real-world setting study, more than 50% of patients retained IV abatacept over 2 years. Higher long-term retention rates were observed when abatacept was initiated earlier in the course of RA. In ACTION, IV abatacept was clinically effective and well tolerated in a broad range of bioexperienced patients. References: Nüβlein H, et al. Arthritis Rheum 2012;64(Suppl10):S199. Disclosure of Interest: H. Nüβlein Consultant for: Bristol-Myers Squibb, Abbott, Chugai, UCB, Essex, Wyeth, Pfizer, MSD, Novartis and Roche, Speakers bureau: Bristol-Myers Squibb, Abbott, Chugai, UCB, Essex, Wyeth, Pfizer, MSD, Novartis and Roche, R. Alten Grant/research support: BMS, Speakers bureau: BMS, M. Galeazzi: None declared, H.-M. Lorenz Consultant for: BMS, Speakers bureau: BMS, M. Nurmohamed Grant/research support: The Jan van Breemen Research Institute has received research grants from Roche, Abbott, Pfizer, UCB and BMS, Consultant for: Roche, Schering-Plough, BMS, UCB, Wyeth, Pfizer and MSD, Speakers bureau: Abbott, Roche, Pfizer and BMS, W. Bensen Grant/research support: Abbott, Amgen, BMS, Janssen, Merck, Lilly, Novartis, Pfizer, Proctor and Gamble, Roche, Sanofi-Aventis, Schering, Takeda, UCB, Warner Chilcott, Wyeth, Consultant for: Abbott, Amgen, BMS, Janssen, Merck, Lilly, Novartis, Pfizer, Proctor and Gamble, Roche, Sanofi-Aventis, Schering, Takeda, UCB, Warner Chilcott, Wyeth, Speakers bureau: Abbott, Amgen, BMS, Janssen, Merck, Lilly, Novartis, Pfizer, Proctor and Gamble, Roche, Sanofi-Aventis, Schering, Takeda, UCB, Warner Chilcott, Wyeth, G.-R. Burmester Grant/research support: Clinical trials for BMS, AbbVie, Pfizer, Medimmune, Novartis, Roche, UCB, Lilly, Consultant for: BMS, AbbVie, Pfizer, MSD, Medimmune, Roche, UCB, Speakers bureau: BMS, Abbott, Pfizer, MSD, Roche, UCB, H.-H. Peter: None declared, K. Pavelka Grant/research support: MSD, Pfizer, Amgen, AbbVie, Roche, Consultant for: MSD, Pfizer, Amgen, AbbVie, Roche, M. Chartier Consultant for: BMS, C. Poncet Consultant for: BMS, C. Rauch Employee of: BMS, M. Le Bars Shareholder of: BMS, Employee of: BMS DOI: 10.1136/annrheumdis-2014-eular.1750